Village Economic Policy Package for Economic Development in Ngusikan Subdistrict, Jombang Regency - Muafiqie, Humaidah; Musta'in, Muhammad Mudjib; Henartiwi, Trusti Dhiani; Aslichah, Aslichah; Raikhani, Agus (International Journal Labs, 2022)
Background: The effects of many economic policy packages aimed at promoting economic growth in Indonesia are thought to have fallen short of expectations. The primary factors are policies that are still reactive and the timing of execution. Aim: This study's goal is to examine how economic development in Jombang's Ngusikan Subdistrict is related to village economic policy packages. Method: This study employed a quantitative methodology with non-experimental fact exposure. Primary information was gathered from surveys of village administrators and local leaders. Secondary data come from documents or directly from linked persons during direct interviews. data analysis utilizing the F-test and simple and fictitious regression correlation analysis. Findings: The development of the economy of Jombang's Ngusikan Subdistrict is significantly influenced by the road and electrical infrastructure. However, in Ngusikan Subdistrict, Jombang District, telephone and water facilities do not significantly affect economic growth. But concurrently, every aspect of the fiscal decentralization strategy has a large impact on the rate of economic expansion in the Ngusikan Subdistrict, Jombang District.